Interdisciplinary Round-Robin Test on molecular spectroscopy of the U(VI) acetate system - Müller, Katharina; Panak, Petra; Skerencak-Frech, Andrej (ACS omega, 2019)
A comprehensive molecular analysis of a simple aqueous complexing system—U(VI) acetate—selected to be independently investigated by various spectroscopic (vibrational, luminescence, X-ray absorption, and nuclear magnetic resonance spectroscopy) and quantum chemical methods was achieved by an international round-robin test (RRT). Twenty laboratories from six different countries with a focus on actinide or geochemical research participated and contributed to this scientific endeavor. The outcomes of this RRT were considered on two levels of complexity: first, within each technical discipline, conformities as well as discrepancies of the results and their sources were evaluated. The raw data from the different experimental approaches were found to be generally consistent. In particular, for complex setups such as accelerator-based X-ray absorption spectroscopy, the agreement between the raw data was high. By contrast, luminescence spectroscopic data turned out to be strongly related to the chosen acquisition parameters. Second, the potentials and limitations of coupling various spectroscopic and theoretical approaches for the comprehensive study of actinide molecular complexes were assessed. Previous spectroscopic data from the literature were revised and the benchmark data on the U(VI) acetate system provided an unambiguous molecular interpretation based on the correlation of spectroscopic and theoretical results. The multimethodologic approach and the conclusions drawn address not only important aspects of actinide spectroscopy but particularly general aspects of modern molecular analytical chemistry.